Strategi Perlindungan Hak Digital Konsumen Dalam Ekosistem E-Commerce Indonesia - Fida Amalia Shofia; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
Digital transformation has revolutionized commercial interactions through e-commerce platforms, simultaneously creating unprecedented challenges in consumer data governance. This research examines strategic frameworks for protecting consumer digital rights, focusing on comprehensive data governance mechanisms within Indonesia's e-commerce ecosystem. Employing mixed-method research combining quantitative analysis of data breach incidents and qualitative assessment of regulatory frameworks, this study analyzes 156 reported data security incidents from 2019-2024. Findings reveal that inadequate data governance structures, insufficient consumer awareness, and weak enforcement mechanisms constitute primary vulnerabilities. The research proposes a multi-tiered protection strategy encompassing regulatory harmonization, technological safeguards, and consumer empowerment initiatives. Key recommendations include establishing a unified data protection authority, implementing mandatory privacy impact assessments, and developing consumer-centric data rights frameworks.